Kemitraan Usaha Sebagai Alternatif Dalam Pembiayaan Sektor Publik Di Daerah: Argumentasi Teoretis dan Kasus Kemitraan Pemerintah-Swasta di Pemda Cirebon dan Pemda Surakarta - Wahyudi Kumorotomo (Faculty of Social and Political Sciences, Universitas Gadjah Mada, 1999)
There have been many promising advantages for the public service schemes based on privatization or partnerships (kemitraan) between the government agencies and the private organizations Along with the newly enacted law on Local Government and the Financial Shares between the Central and Local Governments privatization and kemitraan will be an interesting alternatif for financing public services at the local level.In Indonesia, however, it appears that insofar there are limited local authorities that are experienced in negotiating, implementing and controlling the privatized schemes or the kemitraan. Lack of commitment, political vested interests, and lack of professional attitudes air among the obstacles for the local governments in conducting such schemes. On the other hand, too much profit maximizing, ignorance to the public interest, and low morale would also obstruct the private sectors in serving the best for the public': Nevertheless, such limitations must not avert both sides fivm making political, managerial and technical breakthrough to create a responsive public service system as the privatized and partnership system would be a win-win solution for the government agencies, the private organizations, and the society